Chemistry and basic biomedical sciences. Technological alternative - María Antonia Jiménez Dávila; Yordanis Figueredo Torres; Ismara Zamora León; Irene Luisa del Castillo Remón; Grettel Galiano Guerra; Martha Gertrudis Lara Carrillo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Foundation: the Chemistry teaching-learning process requires constant updating in accordance with the demands of health professionals´ training. Objective: to develop a technological alternative which allows raising the learning level of chemical contents and their practical applications in the health field. Methods: A teaching support educational software was developed to link Chemistry with Basic Biomedical Sciences. Macromedia Flash was used as a design and assembly tool for different modules included in this product. The technological alternative was implemented in the Health Technology training programs that received Chemistry in the 2017-2018 academic year. A quasi experiment with an exit test was applied for the experimental group. Theoretical methods were used: historical-logical, inductive-deductive, analytical-synthetic, systemic-structural-functional and empirical: documentary analysis, surveys, class observation, expert criteria. The participants signed the consent to collaborate and accepted the publication of its results with the guarantee of their anonymity. Results: the results of the quasi-experiment show a qualitative improvement in the students learning in the experimental group. Most of them were placed at a high level of learning by establishing the relationship between molecular cause-disease-practical application of the chemical contents. Conclusions: the implementation of this technological alternative in educational practice allowed raising the learning chemical content level in its practical application in the health field.